Morphological characteristics of rat’s heart at experimental myocardium necrosis. - Shkand, T. V.; Chizh, N. A.; Naumova, O. V.; Sandomirsky, B. P. (Морфологія / Morphologia / Morfologìâ, 2013)
To elucidate pathogenetic mechanisms of myocardium necrosis, to develop the preventive and treatment measures its experimental studying in different models is necessary. The paper covers the dynamics of morphological changes in myocardium after cryoeffect in heart for 15 and 30 sec, ligation of left coronary artery and introduction of adrenalin toxic doses.It has been established that cryoeffect to heart led to the appearance of necrotic zone in myocardium with no ischemic inflammation phase, herewith the depth of cardiac muscle lesion depended directly on cryoeffect duration. The ligation of coronary artery contributed to the formation of ischemic necrosis of myocardium in the zone of ligated vessel basin with manifested discirculatory disorders. Focus lesion of myocardium resulted from the introduction of toxic doses of adrenalin was focused around arterial vessels, which later led to periarterial proliferation of fibroblasts and formation of granulation tissue.